Alternative splicing generates secretory isoforms of human CD1. - Woolfson, A (1994)
Human CD1 genes are a family of five non-polymorphic genes that, although homologous to both class I and II major histocompatibility complex genes, map to chromosome 1. Only three of the antigens, CD1a, -b, and -c, have been clustered with monoclonal antibodies. They are noncovalently associated with beta 2-microglobulin and may function as nonclassical antigen-presenting molecules. Here we analyze their expression in mouse myeloma transfectants and human thymocytes and find mRNA splicing complexity. This manifests itself as incomplete splicing, alternative splicing, utilization of cryptic splice sites, and the generation of alternative reading frames. In the case of CD1A transfectants, we demonstrate that the major protein product is secreted and show by amino acid sequence analysis that this is derived from an unspliced transcript. A second major CD1a component appears to be retained intracellularly. The production of alternatively spliced transcripts in the thymus is not a feature of all CD1 genes. Although in the case of CD1A only the transcript encoding the cell surface CD1a isoform is found, CD1C and -E produce complex intrathymic splicing patterns. The CD1C transcripts predict the expression of a secreted CD1c isoform in the human thymus, which we detect in CD1C transfectant culture supernatants. CD1 gene expression is thus characterized by considerable splicing complexity, and the difference between the splicing patterns found in different environments suggests that this is tissue specific.